EFEKTIVITAS GOOGLE CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR: ANALISIS NILAI SEBELUM DAN SESUDAH IMPLEMENTASI (STUDI KASUS PADA SISWA KELAS XI MAPEL TEKNIK PEMESINAN BUBUT DI SMK N 2 KARANGANYAR) - Febrianti T. Lestari; Budi Murtiyasa; Sukasno; Masduki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This quasi-experimental research examines the impact of Google Classroom integration on academic performance enhancement among grade XI students studying lathe machining technology at SMK Negeri 2 Karanganyar. The study utilized a single-group pretest-posttest methodology with purposive sampling involving 35 vocational education participants across an eight-week implementation phase. Data gathering employed a validated assessment tool containing 40 items (Cronbach's α = 0.951) designed to evaluate theoretical comprehension in lathe machining technology. Statistical examination indicated substantial enhancement in academic achievement following Google Classroom integration, demonstrating mean score progression from 85.57 (SD = 2.963) to 88.37 (SD = 2.808). The Wilcoxon Signed Ranks Test confirmed statistically meaningful variations (Z = -4.705, p < 0.05) between initial and final assessments, with 88.6% of subjects demonstrating academic progress. The platform's success stems from improved student participation, adaptable learning access, individualized educational experiences, and immediate feedback systems. These results provide empirical validation for digital learning management platform effectiveness within vocational educational settings, especially for technical disciplines requiring theoretical knowledge and practical skill integration. This investigation offers evidence-based guidance for enhancing technology-integrated learning environments in vocational educational institutions.